THE IMPACT OF ECO-FRIENDLY INITIATIVES ON EMPLOYEE JOB SATISFACTION AND WELL-BEING IN TOURISM: INVESTIGATING HOW INVOLVEMENT IN GREEN PRACTICES INFLUENCES JOB SATISFACTION AND OVERALL WELL-BEING AMONG EMPLOYEES IN THE TOURISM SECTOR. - Mansukhe, Suresh; Mehta, Megha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines how employee work satisfaction and general well-being in the tourism industry are affected by environmentally friendly activities. An extensive analysis of every facet of employee involvement with sustainable practices indicates a strong correlation between employee job satisfaction and involvement in environmentally friendly projects. Training, resource distribution, and management assistance are all crucial in promoting involvement. Obstacles like ignorance and inadequate rewards come to light as serious issues. The study offers strategies for removing obstacles and maximizing participation, and it highlights the benefits of eco-friendly practices for both business success and employee satisfaction. Future research should concentrate on comparative evaluations and longitudinal studies to advance understanding and application in a range of tourism contexts.